Association between fatty liver index and blood coagulation markers: a population-based study - Maximilian Iglesias Morcillo; Dennis Freuer; Anette Peters; Margit Heier; Daniel Teupser; Christine Meisinger; Jakob Linseisen (Lipids in Health and Disease, 2023)
Abstract Background Population-based studies investigating the association between blood coagulation markers and non-alcoholic fatty liver disease (NAFLD) are rare. Thus, we aimed to investigate the relationship between the Fatty Liver Index (FLI) as a measure of hepatic steatosis and plasma concentrations of antithrombin III, D-dimer, fibrinogen D, protein C, protein S, factor VIII, activated partial thromboplastin time (aPTT), quick value and international thromboplastin time (INR) in the general population. Methods After the exclusion of participants with anticoagulative treatment, 776 participants (420 women and 356 men, aged 54–74 years) of the population-based KORA Fit study with analytic data on hemostatic factors were included in the present analysis. Linear regression models were used to explore the associations between FLI and hemostatic markers, adjusted for sex, age, alcohol consumption, education, smoking status, and physical activity. In a second model, additional adjustments were made for the history of stroke, hypertension, myocardial infarction, serum non-HDL cholesterol levels, and diabetes status. In addition, analyses were stratified by diabetes status. Results In the multivariable models (with or without health conditions), significantly positive associations with FLI were obtained for plasma concentrations of D-dimers, factor VIII, fibrinogen D, protein C, protein S, and quick value, while INR and antithrombin III were inversely associated. These associations were weaker in pre-diabetic subjects and largely disappeared in diabetic patients. Conclusion In this population-based study, an increased FLI is clearly related to changes in the blood coagulation system, possibly increasing the risk of thrombotic events. Due to a generally more pro-coagulative profile of hemostatic factors, such an association is not visible in diabetic subjects.